2021
DOI: 10.1080/21642850.2021.1968301
|View full text |Cite
|
Sign up to set email alerts
|

Gender and pandemic perception: analyzing perceived risk and fear among Brazilian women

Abstract: Objective The World Health Organization has warned of the importance of looking at the pandemic from a gender perspective since biological, social, and cultural aspects can produce differences in the way women and men experience the ongoing pandemic situation. This study aimed to investigate Brazilian women’s perception of COVID-19 concerning the susceptibility to infection, the severity of COVID-19, and the collective behavior in response to pandemic risks. It also sought to examine the COVID-19 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 29 publications
1
6
1
1
Order By: Relevance
“…The more the women were entered into interpersonal relationships, the greater the fear of infection was. It has also been indicated that there is a higher level of fear among those women who are responsible for their loved ones and live in a family [52]. It is especially true for mothers of young children and pregnant women, as confirmed by studies and meta-analyses conducted in many countries around the world [53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 96%
“…The more the women were entered into interpersonal relationships, the greater the fear of infection was. It has also been indicated that there is a higher level of fear among those women who are responsible for their loved ones and live in a family [52]. It is especially true for mothers of young children and pregnant women, as confirmed by studies and meta-analyses conducted in many countries around the world [53][54][55][56][57].…”
Section: Discussionmentioning
confidence: 96%
“…We found that gender and age were associated with the perceived severity of COVID-19, which is consistent with previous studies. Giordani et al [ 27 ] reported that women perceived COVID-19 as more life-threatening than men, and this perception was more pronounced among women aged 30-59 and 60 or older. Similarly, another study found that women were more anxious about COVID-19 than men [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Summing this up to formal work, poorer women have been suffering from a double burden of activities for a long time. During the pandemic (with lockdowns and “stay at home” policies), that pattern increased gender inequalities, reducing women’s leisure time and, consequently, may decreased physical activity levels (Giordani et al 2021; Wenham et al 2020).…”
Section: Discussionmentioning
confidence: 99%